2019
DOI: 10.1016/j.ypmed.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using social media to monitor outdoor air pollution in London, England

Abstract: Air pollution is a serious public health concern. Innovative and scalable methods for detecting harmful air pollutants such as PM2.5 are necessary. This study assessed the feasibility of using social media to monitor outdoor air pollution in an urban area by comparing data from Twitter and validating it against established air monitoring stations. Data were collected from London, England from July 29, 2016 to March 17, 2017. Daily mean PM2.5 data was downloaded from the LondonAir platform consisting of 26 air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…With such large volume of real-time data, social media has become an important data source in both industry and academia. It is extensively used in a wide range of topics, including monitoring outdoor air pollution in London [3], modeling rumor spreading [4,5], preventing sensitive information attacks, achieving disease surveillance [6], detecting natural disasters [7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…With such large volume of real-time data, social media has become an important data source in both industry and academia. It is extensively used in a wide range of topics, including monitoring outdoor air pollution in London [3], modeling rumor spreading [4,5], preventing sensitive information attacks, achieving disease surveillance [6], detecting natural disasters [7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The association between energy and environmental pollution and energy and environment efficiency have been widely studied (Hu and Wang, 2006;Yeh et al, 2010;Song et al, 2013;Wu et al, 2015;Li and Du, 2015;Meng et al, 2016;Yao et al, 2016;Abbas et al, 2017;Qin et al, 2017;Feng et al, 2017;Hu et al, 2017;Mehmeti et al, 2018), with some studies identifying the factors that affect energy efficiency (Bampatsou et al, 2013;Li et al, 2013;Lin and Du, 2015;Li and Lin, 2017;Du et Al., 2017;Wang et al, 2017;Jebali et al, 2017), and others exploring the relationship between air pollution, the environment and the mass media (McCreery, 2010;Mayer, 2012;Chen, 2014;Kay et al, 2015;Hswen et al, 2019). Some scholars have also studied the effects of news media reports on improving the public's awareness of environmental protection and environmental protection (Lowe and Morrison, 1984;McCreery, 2010;Niklas et al, 2011;Marianne and Mason, 2012;Wang et.…”
Section: Introductionmentioning
confidence: 99%
“…examined the corporate environmental reporting of 100 companies in promoting social responsibility for groups such as employees and shareholders and members outside the group such as consumers, Chen (2014) analyzed reports from China's official English-language newspaper, the China Daily, on air pollution in China in 2013, and Wang et al (2015)studied Chinese social media to monitor air quality trends and related public perceptions and responses, finding that the information on Weibo reflected the true level of particle pollution Kay et al (2015). took Sina Weibo as a research object and concluded that it effectively promoted public environmental awareness,Kerrie and Claire (2018) found that the Australian news media played an important role in protecting coral reefs, andHswen et al (2019) found that social media could aid in environmental monitoring.…”
mentioning
confidence: 99%
“…As an increasing number of people are voicing their feelings and opinions about their living environments on social media, it has proven feasible and effective to use social media data to monitor the quality of the environment, including air pollution, which has long been a serious public health issue [8][9][10]. Performing a sentiment analysis on social media data to extract public opinions also provides a new data source and a new method for tourism research [11].…”
Section: Introductionmentioning
confidence: 99%